The art of the confectioner : sugarwork and pastillage - Notter, Ewald , 1955- (John Wiley & Sons, 2012)
A gorgeous professional-level guide to the most challenging form of the confectioner's art A showpiece created entirely from sugar is truly a work of art, and it takes an eye for design and strong pastry skills to work with this delicate medium